Postpartum Urinary Retention after Vaginal Delivery: Retensi Urine pada Pasien Pascasalin Pervaginam - Bonifacius B Erlangga; Rudy A Lengkong; John Wantania (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective:To determine the incidence of postpartum urinary retention (PUR) after vaginal delivery and to specify any obstetric risk factors that contributing PUR. Methods: Case control study. Six hours after vaginal delivery, urethral catheterization was implemented for estimation of post void residual bladder and diagnosis PUR. Patient data, including age, gestational age, body mass index, parity, mode of delivery, labor duration, perineal laceration or episiotomy, and fetal birth weight, were compared between women with and those without PUR to determine which obstetric factors that develops PUR. Results: Of the 365 participants recruited, 38 (10,67%) had PUR: 33 (9,27%) with covert PUR and 5 (1,4%) with overt PUR. Women with perineal laceration or episiotomy (p<0,05), instrument-assisted delivery (p<0,05), first stage duration of labor more than 12 hours (p<0,05), second stage duration of labor more than one hour in multipara (p=0,041), and fetal birth weight more than 3800 grams (p<0,05) more prone to develop PUR. Conclusion: The incidence of PUR were associated with several obstetric risk factors: perineal laceration or episiotomy, instrument-assisted delivery, first stage duration of labor more than twelve hours, second stage duration of labor more than one hour in multipara, and fetal birth weight more than 3800 grams. Key words: vaginal delivery, postpartum urinary retention, risk factor Abstrak Tujuan:Mengetahui angka kejadian retensi urine di kota Manado dan mengetahui faktor risiko obstetri yang berperan dalam terjadinya retensi urine pascasalin pervaginam. Metode:Penelitian kasus kontrol. Dilakukan pemeriksaan residu urine 6 jam pascasalin pervaginam untuk mengetahui kejadian retensi urine. Data pasien yang diambil berupa usia, usia gestasi, indeks massa tubuh, paritas, jenis persalinan, durasi kala I, durasi kala II, laserasi perineum / episiotomi, dan berat badan lahir bayi kemudian dibandingkan antara yang menderita retensi urine dan tanpa retensi urine pasca salin untuk mengetahui faktor risiko obstetri yang berperan. Hasil:Dari 365 sampel penelitian, 38 (10,67%) menderita retensi urine: 33 (9,27%) retensi urine asimptomatis dan 5 (1,4%) retensi urine simptomatis. Pasien dengan laserasi perineum / episiotomi (p<0,05), persalinan dengan bantuan instrumen (p<0,05), durasi persalinan kala I ³ 12 jam (p<0,05), persalinan kala II ³ 1 jam pada multipara (p=0,041), dan berat badan lahir bayi ³ 3800 gram (p<0,05) memiliki risiko lebih tingi menderita retensi urine pascasalin pervaginam. Kesimpulan:Kejadian retensi urine pascasalin pervaginam berhubungan dengan beberapa faktor risiko obstetri yaitu laserasi perineum / episiotomi, persalinan dengan bantuan instrumen, durasi persalinan kala I ³ 12 jam, persalinan kala II ³ 1 jam pada multipara, dan berat badan lahir bayi ³ 3800 gram. Kata kunci: persalinan pervaginam, retensi urine, faktor risik